Determinants of Street Entrepreneurial Success - Thapa, Ajay; Thulaseedharan, Archana; Goswami, Arup; Joshi, Lucky Prasad (Journal of Nepalese Business Studies, 2009)
Street entrepreneurship is one of the rapidly growing areas in the present business world. Understanding the factors affecting this business is important for the business people. This study has revealed many facts concerning the socio-economic and motivational factors affecting street entrepreneurship. Among many socio-economic and motivational factors, size of initial investment, number of workers, family business and promising demand of product/services are some of the major determinants of street entrepreneurial success. The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page: 85-92